Widespread Decreases in Cerebral Copper Are Common to Parkinson's Disease Dementia and Alzheimer's Disease Dementia - Scholefield, Melissa; Church, Stephanie J.; Xu, Jingshu; Patassini, Stefano; Roncaroli, Federico; Hooper, Nigel M.; Unwin, Richard D.; Cooper, Garth J. S. (Frontiers in Aging Neuroscience, 2021)
Several studies of Parkinson’s disease (PD) have reported dysregulation of cerebral metals, particularly decreases in copper and increases in iron in substantia nigra (SN). However, few studies have investigated regions outside the SN, fewer have measured levels of multiple metals across different regions within the same brains, and there are no currently-available reports of metal levels in Parkinson’s disease dementia (PDD). This study aimed to compare concentrations of nine essential metals across nine different brain regions in cases of PDD and controls. Investigated were: primary motor cortex (MCX); cingulate gyrus (CG); primary visual cortex (PVC); hippocampus (HP); cerebellar cortex (CB); SN; pons including locus coeruleus (LC); medulla oblongata (MED); and middle temporal gyrus (MTG) , thus covering regions with severe, moderate, or low levels of neuronal loss in PDD. Levels of nine essential metals were determined using a reference method, inductively-coupled plasma mass spectrometry (ICP-MS), and compared between cases and controls , to better understand the extent and severity of metal perturbations. Findings were also compared with those from our previous study of sporadic Alzheimer’s disease dementia (ADD), which employed equivalent methods, to identify differences and similarities between these conditions. Widespread copper decreases occurred in PDD in seven of nine regions (exceptions being LC and CB). Four PDD-affected regions showed similar decreases in ADD: CG, HP, MTG, and MCX. Decreases in potassium and manganese were present in HP, MTG and MCX; decreased manganese was also found in SN and MED. Decreased selenium and magnesium were present in MCX, and decreased zinc in HP. There was no evidence for increased iron in SN or any other region. These results identify alterations in levels of several metals across multiple regions of PDD brain, the commonest being widespread decreases in copper that closely resemble those in ADD, pointing to similar disease mechanisms in both dementias.